Pengaruh Penerapan Sistem Informasi Akuntansi Dan Teknologi Informasi Terhadap Kinerja UMKM Di Kota Pekanbaru - Liza Ulfiana; Nurhayanti; Nurhayati Lubis; Alputri Oktavia (Hikamatzu | Journal of Multidisciplinary, 2026)
This study used a sample of 394 respondents. Based on the results of the t- and f-tests, it was concluded that, partially or individually, the information system variable influences the performance of Micro, Small, and Medium Enterprises, while the information technology variable, based on the partial or individual test results, influences the performance of Micro, Small, and Medium Enterprises. The simultaneous test results for the accounting information system and information technology variables significantly influence the performance of Micro, Small, and Medium Enterprises in Pekanbaru City.